Laparoscopic and Endoscopic cooperative surgery as Rescue-treatment for Advanced gastric Cancer in patients Unfit for Surgery (LE-RACUS): protocol for a feasibility study - Henrik Maltzman; Masami Omae; Fredrik Klevebro; Francisco Baldaque-Silva; Ioannis Rouvelas (Pilot and Feasibility Studies)
Abstract Background The standard treatment for advanced gastric cancer without metastasis is gastrectomy in combination with chemotherapy. Some patients cannot tolerate such treatment because of old age or comorbidities. In this study, we want to test the feasibility of Laparoscopic and Endoscopic Cooperative Surgery (LECS) as a less invasive treatment option. In LECS, the tumor margin is marked endoscopically, followed by surgical removal under endoscopic guidance. Currently, LECS is primarily used in Asian countries as a treatment for gastrointestinal stromal cell tumors. Methods The study will be conducted as a prospective single-center, feasibility trial. The primary objective will be the safety of LECS, defined as Clavien-Dindo score ≥ III. The secondary objectives will be any complications, postoperative bleeding/perforation, operation time, radicality, mortality, hospital stay, and health-related quality of life. The inclusion criteria will be patients with gastric cancer cT2-T4aN0M0, Borrman type 1–2 < 5 cm, or type 3 < 2 cm that the tumor board assesses as not fit for gastrectomy. Exclusion criteria will be Borrman type 4 and lesions in the cardia. The patients will be followed up with an outpatient appointment 30 days after the procedure. Discussion LECS is a promising treatment option for patients with gastric cancer who cannot tolerate gastrectomy. Compared to gastrectomy, LECS is a less invasive procedure with a documented low complication rate. No previous prospective studies have been conducted to evaluate LECS for advanced gastric cancer. Trial registration ClinicalTrials.gov identifier: NCT06105515. Registered 23 October 2023. https://clinicaltrials.gov/study/NCT06105515?cond=Gastric%20Cancer&term=NCT06105515&aggFilters=status:not%20rec&rank=1